Combining the Generalized Complementary Relationship and the Modified Priestley-Taylor Equation to estimate and partition the evapotranspiration of typical plantations and grasslands in the Loess Plateau of China - Chong Fu; Xiaoyu Song; Lanjun Li; Xinkai Zhao; Pengfei Meng; Long Wang; Wanyin Wei; Nan Yang; Huaiyou Li (Agricultural Water Management, 2023)
Identifying the unique change characteristics of evapotranspiration (ET) in the typical vegetation of the semi-arid Loess Plateau and accurately estimating their components, namely evaporation (E) and transpiration (T), poses a challenging work. The typical vegetation consists of Robinia pseudoacacia (RP), Platycladus orientalis (PO), Mixed plantation of RP and PO (MP), Constructed grassland (CG), and Natural grassland (NG). This study constructed a practical framework for ET partition by utilizing the Generalized Complementary Relationship (GCR) and the Modified Priestley-Taylor Equation (MPTE) to estimate actual ET and T, respectively, and E can be obtained as the difference between ET and T. The results indicated that the Dynamic Scaling of the GCR (S2017) performed with the highest accuracy at watershed scales by simultaneously adjusting the non-α parameters and assigning different fixed αe values in different hydrological years. Its simulated values (ETa17) exhibited an extremely significant sigmoid function relationship with the actual ET of different vegetation (ET’aw) at plot scales (R2 > 0.88). The Priestley-Taylor coefficient, αc, used to estimate T of plantations and grasslands, showed significant logarithmic and quadratic polynomial response functions to precipitation (P) (R2 > 0.75), respectively. The combined method displayed high accuracy in estimating ET and its components for plantations and grasslands, with NSE exceeding 0.7 for the whole period. It is noteworthy that this level of performance could be achieved with minimal data requirements [Rn, u, Ta, RH or Td, P, LAI]. The ET’aw and its components increased with the moisture of the environment on the whole but were inconsistent with P on weekly scales. The variations of soil water storage (ΔW) showed negative in single plantations and positive in grasslands, while close to balance in the mixed plantation in one hydrological cycle (CG > NG > MP ≈ 0 > PO > RP). And ΔW of the whole period (2015–2020) showed negative in single plantations and positive in grasslands (CG larger) and mixed plantation. The order of T/ET was MP > RP > PO > CG > NG, with MP and CG maintaining relatively stable T in different hydrological years. These findings suggested that with reasonable control measures, a mixed planting plan of mixed plantation and constructed grassland may be an excellent solution for alleviating the pressure of water resources management and fostering ecological restoration in the future.